Analysis of Errors and Winners in Men’s and Women’s Professional Padel - Adrián Escudero-Tena; Diego Muñoz; Bernardino Javier Sánchez-Alcaraz; Javier García-Rubio; Sergio J. Ibáñez (Applied Sciences, 2022)
The objective was to analyze the effectiveness in men’s and women’s professional padel of errors and winners depending on the type of shot and the importance of the situation during each game. In addition, differences between men and women were identified. The sample was made up of 2759 points corresponding to the games that finished with a golden point from matches played in the 2021 season of the World Padel Tour circuit. The results show men and women make more errors (men: 58.7%; women: 63.2%) than winners (men: 41.3%; women: 36.8%), and this difference increases as the importance of the points increases in men’s padel; however, the opposite happens in women’s padel. Trays and smashes are the most characteristic last shots in men’s and women’s padel (hits with which more winners are achieved), followed by back wall shots (shots where more errors are made) and then drive and backhand volleys. In men’s padel there are more winning shots and fewer errors than in women’s padel, except in the golden points, where men make more errors than women. These considerations are of great importance, as they help the players to know the most effective way to finish points according to the situation of the game.